1999
DOI: 10.1159/000014387
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Production in Haemodialysis

Abstract: Many aspects regarding morbidity and mortality of dialysis patients are related to the production of cytokines by peripheral blood mononuclear cells. Clinical alterations resulting from cytokine production and release may include dialysis amyloidosis, malnutrition and atherogenesis. Cytokine release may also play a relevant role in immunodeficiency of dialysis patients by inducing alterations in immune and host-defense system. Interleukin-1, interleukin-6 and tumor necrosis factor are three pro-inflammatory cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 88 publications
(101 reference statements)
0
21
0
Order By: Relevance
“…Although the 'earlystart hypothesis' may seem attractive it could not be ruled out that the dialysis procedure actually might aggravate systemic inflammation as available evidence from crosssectional studies suggests that the prevalence of elevated CRP is higher in HD than predialysis patients (table 1). Although the occurrence of pyrogenic reactions due to passage of endotoxins, or endotoxin fragments, has decreased in the recent years, monocyte activation with subsequent cytokine production may still take place during the dialysis procedure [83]. Haubitz et al [84] have demonstrated that acute-phase proteins are induced during HD, probably due to cytokine release, and according to Schindler et al [85] the dialyser membrane may play a role in the induction of an inflammatory reaction during the dialysis procedure.…”
Section: Does the Dialysis Procedures Per Se Accelerate The Atherosclementioning
confidence: 99%
“…Although the 'earlystart hypothesis' may seem attractive it could not be ruled out that the dialysis procedure actually might aggravate systemic inflammation as available evidence from crosssectional studies suggests that the prevalence of elevated CRP is higher in HD than predialysis patients (table 1). Although the occurrence of pyrogenic reactions due to passage of endotoxins, or endotoxin fragments, has decreased in the recent years, monocyte activation with subsequent cytokine production may still take place during the dialysis procedure [83]. Haubitz et al [84] have demonstrated that acute-phase proteins are induced during HD, probably due to cytokine release, and according to Schindler et al [85] the dialyser membrane may play a role in the induction of an inflammatory reaction during the dialysis procedure.…”
Section: Does the Dialysis Procedures Per Se Accelerate The Atherosclementioning
confidence: 99%
“…Patients who underwent hemodialysis (HD) were also in a state of chronic infl ammation [7][8][9] . Recently, we found that serum levels of IL-18 were higher in dialysis patients and were associated with poor outcome.…”
mentioning
confidence: 99%
“…It has been suggested that some dialysis-related alteration in the immune and host-defense system may be relevant, as they seem to correlate to the high production of proinflammatory cytokines (8). Moreover, the type of dialysis membrane has been suggested to play a role (9) as well as time on dialysis, as it correlated negatively with cytokine release (10).…”
mentioning
confidence: 99%